PTH-127 Prevalence of joint hypermobility syndrome in patients with functional gastrointestinal disorders in an asian tertiary gastroenterology unit. (17th June 2017) - Ong, AML; Lim, CH; Wang, YT
Abstract : Introduction: Functional gastrointestinal disorders (FGID) are prevalent in the general population worldwide and constitute a large healthcare burden. Recently a high incidence of joint hypermobility syndrome (JHS) which is synonymous with Ehlers-Danlos Syndrome- Hypermobility Type, was reported in a group of patients with FGID in the United Kingdom. Our aim is to determine the prevalence of JHS among FGID patients in an Asian population. Method: Case controlled study design was adopted. FGID patients who fulfilled the ROME III criteria for either Irritable bowel syndrome (IBS) or functional dyspepsia (FD) were recruited from the outpatient clinic of a gastroenterology unit at a teaching hospital in Singapore. The control cases were patients who were attending the clinic with other diagnoses. JHS was diagnosed based on the Revised Brighton Criteria and joint measurements were performed by blinded assessors. Symptom severity was assessed with Gastrointestinal Symptom Rating Scale(GSRS) and Quality of life with EQ-5D. In a subset of FGID patient (n=27), gastrointestinal transit time(GIT) was measured using wireless motility capsule and small intestinal bacterial overgrowth was measured with glucose hydrogen breath test (HBT). T-test was used to assess continuous variables and Fisher exact test for categorical variables. Results: 130 FGID patients and 79 controls (most common diagnoses were chronic hepatitis B and non- alcoholic fatty liver disease) were recruited between 1 st January 2014 and 20th January 2016. There were more females in the FGID group 69% vs Control Group 32% (p-value<0.0001), The FGID group was younger (Median: 46 (SD: 13) Vs 54 (12), p-value=0.0001); but the race distribution were similar, the predominant race in both groups was Chinese: FGID 88% Vs 96% in Control group. 109 FGID and 78 controls with completed data were analysed. JHS is more prevalent among the FGID 13%, there was no JHS among the controls (p=0.001). FGID diagnoses among JHS patients were: FD (JHS 14% Vs 39% non-JHS, p=0.035), IBS (29% Vs 25%, p=0.81) and Overlap (57% Vs 36%, p=0.16). 14% of JHS patients reported severe pain (GSRS ≥4) Vs 6% in non-JHS (non-significant). Quality of life (EQ-5D) was similar between the 2 groups. GIT was abnormal in 66% (2/3) of JHS Vs 55% (13/24) (p=0.69) in non-JHS. 33%( 1/3) JHS Vs 21%( 5/24) (p=0.64) non-JHS had positive HBT. Conclusion: JHS is more prevalent among FGID patients in a predominant Chinese cohort in an Asian tertiary gastroenterology unit compared to a control group and these patients appear to have abnormalities in transit and small intestinal bacterial overgrowth. Further studies are needed to characterise these patients further and understand the role of connective tissue in gastrointestinal function. Disclosure of Interest: None Declared